Startup communities : building an entrepreneurial ecosystem in your city - Feld, Brad. (Hoboken, New Jersey : John Wiley & Sons, Inc., 2012)
"'Startup communities' are popping up everywhere, from cities like Boulder to Boston and even in countries such as Iceland. These types of entrepreneurial ecosystems are driving innovation and small business energy. Startup Communities documents the buzz, strategy, long-term perspective, and dynamics of building communities of entrepreneurs who can feed off of each other's talent, creativity, and support. Based on more than twenty years of Boulder-based entrepreneur turned-venture capitalist Brad Feld's experience in the field, as well as contributions from other innovative startup communities, this reliable resource skillfully explores what it takes to create an entrepreneurial community in any city, at any time. Along the way, it offers valuable insights into increasing the breadth and depth of the entrepreneurial ecosystem by multiplying connections among entrepreneurs and mentors, improving access to entrepreneurial education, and much more"--Provided by publisher
Foreword -- Preface -- Acknowledgments -- Introduction -- The boulder startup communities -- Principles of a vibrant startup community -- Participants in a startup community -- Attributes of leadership in a startup community -- Classical problems -- Activities and events -- The power of accelerators -- University involvement -- Contrasts between entrepreneurs and government -- The power of the community -- Broadening a successful startup community -- Myths about startup communities -- Getting started -- About the author -- Index.
Includes index.
Print version record and CIP data provided by publisher.
John Wiley and Sons
Keywords: Entrepreneurship; New business enterprises -- Environmental aspects; Communities -- Social aspects; Entrepreneurship; Entrepreneuriat; Nouvelles entreprises -- Aspect de l'environnement.; x; entrepreneurs; BUSINESS & ECONOMICS -- Development -- Business Development; BUSINESS & ECONOMICS -- New Business Enterprises; Communities -- Social aspects; Entrepreneurship; dissertations; Academic theses; Academic theses; 2